Development of Agricultural Tourism Destinations as a Community Creative Economy in the Bekasi Regency Area - Muhamad Syahwildan; Muhamad Ekhsan (Privietlab, 2021)
This journal describes the results of community service activities in the form of a national online seminar on village tourism as the community's creative economy. This activity is motivated by the people's unconsciousness of the potential of their village. The purpose of this activity is to open the mindset of the local community that Karangmukti Village has an agricultural tourism object that has a great opportunity if it is developed seriously. Therefore, we organize online seminars related to village tourism as a community creative economy. By organizing these online seminars, it is hoped that the community will pay more attention to the opportunities that exist in Karangmukti village and can be moved to develop village tourism as one of the objects that can help improve the community's economy. The results obtained from these activities are that communication has been established between related stakeholders. For the next stage, the village government and the community are expected to follow up on existing communications to be able to develop agricultural tourism in the area.